Sequencing-Based Transcriptome-Wide Targeted Genotyping for Evolutionary and Ecological Studies. (March 2019) - Zhu, Xuan; Wang, Jing; Lv, Jia; Liu, Pingping; Zhang, Lingling; Jiao, Wenqian; Ma, Cen; Bao, Zhenmin; Wang, Shi
Transcriptome-wide targeted genotyping is highly attractive for evolutionary and ecological studies but, until recently, accomplishing this goal presented a major technical barrier for the study of non-model organisms. Our group has recently developed a high-throughput targeted genotyping approach (called HD-Marker) based on the high specificity and accuracy of oligo extension-ligation assays that facilitates the design of assays tailored to meet specific genotyping needs. HD-Marker allows for targeted genotyping of over 10 000 genes in a single tube, with strikingly high capture rate (98%-99%) and genotyping accuracy (97%-99%). With the remarkable advantages of cost-effectiveness and flexibility, we envision that HD-Marker has broad application potential in evolutionary and ecological studies.